2021
DOI: 10.24996/ijs.2021.62.7.11
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Chaotic Dynamics Using Rossler-Chua Systems Combined with A Semiconductor Laser

Abstract: In this paper, two different chaotic dynamic systems are coupled using a semiconductor laser to produce a new chaotic system. These two chaotic systems are Rossler and Chua systems. X-dynamic of Rossler system was coupled optically using optical fiber as a carrier of signal with x, y, and z-dynamics of Chua system. The results were analyzed and the behavior of Chua system was found to be changing in time series which, in turn, changed the attractor. The Chua attractor was converted from double scroll to single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…When applying the correlation relationship between the two chaotic systems at this value of the correlation factor, we get a straight line inclined at an angle of o 45, and this is clear evidence of the complete synchronization between the two systems, and this is evident in Figures (19), ( 20) and ( 21). Now, after obtaining complete synchronization between the two chaotic systems, it is possible to send and receive any external messages without any distortion occurring in them, and this is evident in Figure (22), where the signal in is black line and signal out is blue line at coupling factor k equal 270 (synchronization), amplitude and frequency of signal in are 0.01 and 0.1.…”
Section: (γ) ϵ) δmentioning
confidence: 99%
See 2 more Smart Citations
“…When applying the correlation relationship between the two chaotic systems at this value of the correlation factor, we get a straight line inclined at an angle of o 45, and this is clear evidence of the complete synchronization between the two systems, and this is evident in Figures (19), ( 20) and ( 21). Now, after obtaining complete synchronization between the two chaotic systems, it is possible to send and receive any external messages without any distortion occurring in them, and this is evident in Figure (22), where the signal in is black line and signal out is blue line at coupling factor k equal 270 (synchronization), amplitude and frequency of signal in are 0.01 and 0.1.…”
Section: (γ) ϵ) δmentioning
confidence: 99%
“…The synchronization term can be represented by coupling term where k is coupling factor. Through previous experiments [1,6,7,[11][12][13][14][15][16][17][18][19][20][21][22], it was found that it is better to perform the synchronization process on the y2 channel, and to send the external message on the x1 channel, as follow:…”
Section: A Novel Secure Communication Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…If the function F(ξ,η) is a object function, then the Fourier transform of it will be represented by the function G (x,y). then [15] 1 where x and y = 0,1,2,3……N − 1.…”
Section: Constriction Hologrammentioning
confidence: 99%
“…One of these works of literature has employed image encryption methods due of its large and complicated data. Using Chaos-based systems, which prevent unauthorized access to data transferred between locations [5][6][7][8][9][10][11][12][13][14][15][16]. Many encryption methods were used in the past, including circular mapping with two keys and an unorganized logistics map [17].…”
Section: Introductionmentioning
confidence: 99%